Single-Arm, Non-randomized, Time Series, Single-Subject Study of Fecal Microbiota Transplantation in Multiple Sclerosis - Engen, Phillip A.; Zaferiou, Antonia; Rasmussen, Heather; Naqib, Ankur; Green, Stefan J.; Fogg, Louis F.; Forsyth, Christopher B.; Raeisi, Shohreh; Hamaker, Bruce; Keshavarzian, Ali (Frontiers in Neurology, 2020)
Emerging evidence suggests intestinal microbiota as a central contributing factor to the pathogenesis of Relapsing-Remitting-Multiple-Sclerosis (RRMS). This novel RRMS study evaluated the impact of fecal-microbiota-transplantation (FMT) on a broad array of physiological/clinical outcomes using deep metagenome sequencing of fecal microbiome. FMT interventions were associated with increased abundances of putative beneficial stool bacteria and short-chain-fatty-acid metabolites, which were associated with increased/improved serum brain-derived-neurotrophic-factor levels and gait/walking metrics. This proof-of-concept single-subject longitudinal study provides evidence of potential importance of intestinal microbiota in the pathogenesis of MS, and scientific rationale to help design future randomized controlled trials assessing FMT in RRMS patients.